PENGARUH STRATEGI PEMBELAJARAN RECIPROCAL TEACHING TERHADAP KEMAMPUAN BERPIKIR KRITIS BIOLOGI SISWA SMA ISLAM AL – MA’ARIF SINGOSARI MALANG - Dwi candra setiawan; A D Corebima; Siti Zubaidah (BIODIK, 2016)
ABSTRACT. The objectives of this research were to explain the influence of RT strategy towards critical thinking. Quasi-expermental with Pretest-Postest Nonequivalent Control Group Design was used in this research. The independent variable was teaching strategy (reciprocal teaching). The dependent variable was metacognitive competence, critical thinking, and the understanding of concept. The population of this research was all of the students of grade X of SMAI Al Ma’arif singosari, Malang. The sample of this research was the students of grade X-1 as an experimental group and the students of X-4 as a control group. Critical thinking was measured by an essay test. The validity and the reliability of the instruments were firstly tested. The data were taken in pretest-posttest. Anakova was used in the hypothesis test with the significance level 0.05 (P<0.05). The results of this research showed that teaching strategies influenced critical thinking. Regarding with the potential of RT, it is suggested that this strategy could be implemented so that students’ competencies, besides cognitive domain, could be empowered Key words: Reciprocal Teaching, critical thinking